The Use of Third Party Services in the Protection of Foundation Funds in Indonesia - Sally Novita Nia (Borong Newinera Publisher, 2023)
The foundation is a legal entity engaged in the social, humanitarian and religious fields. The Foundation has no members. Judging from its purpose, the foundation is not looking for profit. Foundations have an independent position as a result of having assets that are separate from the personal wealth of the founders and administrators, and have their own goals that are different or separate from the personal goals of the founders or administrators. In the article 7 of the Law states that foundations can participate in various forms of business that are prospective, provided that all participation is at most 25% (twenty five percent) of the total value of the foundation's assets. In practice, there have been irregularities in the management of funds and the misuse of foundations. This paper will examine how to manage foundation funds so that there are no irregularities in the foundation's legal entity. In the management of foundation activities, it can be made in the form of written activities before carrying out social activities for the foundation.